Impact of corporate political activity on the relationship between corporate social responsibility and financial performance: a dynamic panel data approach - Lin, Woon Leong; Jo, Ann Ho; Sambasivan, Murali (MDPI AG, 2019)
As corporate social responsibility (CSR) gains momentum in the business world, it is imperative to comprehend the relationship between CSR and corporate financial performance (CFP). While there is prior research looking at this relationship, scholars have proposed a contingency view that is meant to determine the situational contexts in which critical associations between CFP and CSR activities will arise. This study provides further insight into the moderating effects of corporate political activity, specifying the ways in which different arrangements of corporate CSR and CPA might align or otherwise, thus influencing CFP beyond associated dissimilar effects on corporate performance. The data for this study was obtained for the periods 2007–2016 from the samples selected from the list of Fortune’sWorld’s Most Admired Companies. The dynamic panel data was analyzed using the System Generalized Method of Moment estimation. The main findings are that CSR does not significantly influence CFP. However, CPA does negatively moderate the relationship between CSR and CFP. This indicates that high political expenditures worsen a firm’s financial.